Policy Persistence and Rent Extraction - Silke Friedrich (Center for Economic Studies and ifo Institute (CESifo), 2013)
The existing literature has shown that special interest groups can have both growth enhancing and retarding effects on an economy. In either case it is always assumed that the nature of the special interest groups remains constant over time. The hypothesis of this paper is that a dynamic relationship exists between politicians and lobbyists. In the short run politicians may choose to support projects proposed to them by lobbies, because they yield clear economic benefits. However, governmental support may continue after these benefits have been exhausted, implying a cost to society and yielding private rents to the lobbies. A theoretical framework in which established and new lobbies overlap is developed to model the incentives a government might have to behave in a manner consistent with the hypothesis. In this structure despite the fact that politicians support projects from which all productive benefits have been extracted the voters can still rationally reelect them.
Keywords: D72; 330; lobby; special interest; efficiency; elections